Editorial Introduction to the Northeast Journal of Complex Systems (NEJCS) - Hiroki Sayama; Georgi Georgiev (Northeast Journal of Complex Systems, 2019)
Editorial Introduction to the Northeast Journal of Complex Systems (NEJCS)